Vaspin suppresses cytokine-induced inflammation in 3T3-L1 adipocytes via inhibition of NFκB pathway. (15th January 2018) - Zieger, Konstanze; Weiner, Juliane; Krause, Kerstin; Schwarz, Maximilian; Kohn, Martin; Stumvoll, Michael; Blüher, Matthias; Heiker, John T.
Abstract: Vaspin expression is increased in white adipose tissue (WAT) of diet-induced obese mice and rats and is supposed to compensate HFD-induced inflammatory processes and insulin resistance in adipose tissue by counteracting pro-inflammatory gene expression in obesity. Multiple studies have also demonstrated strong anti-inflammatory effects in vascular and skin cells. Here, we used vaspin treated 3T3-L1 murine adipocytes as well as 3T3-L1 cells with stable vaspin expression to investigate the effect of exogenous and endogenous vaspin on inflammatory processes and insulin signaling in adipocytes. Our stably transfected cells secreted significant amounts of vaspin which was in the physiological range of ∼0.5 ng/ml in cell supernatants. Adipocyte differentiation was not affected by vaspin as expression of adipogenic marker genes as well as lipid accumulation after full differentiation was similar to control cells. We found that IL-1β induced expression and secretion of pro-inflammatory cytokines, such as IL-6, MCP1 and TNFα was significantly blunted in vaspin expressing 3T3-L1 cells. Treatment of 3T3-L1 cells with exogenous vaspin resulted in reduced cytokine-induced activation of the intracellular and pro-inflammatory NFκB signaling cascades (IKKα/β, IκB and NFκB). Moreover, endogenous vaspin positively affected insulin signaling by increasing insulin-stimulated phosphorylation of the key mediator protein kinase B (AKT). Together, we demonstrate anti-inflammatory effects of vaspin in 3T3-L1 adipocytes as well as increased insulin signaling by endogenous expression or exogenous treatment. The results provide evidence for potent anti-inflammatory action of vaspin not only in vascular cells but also in adipose tissue. Highlights: Direct anti-inflammatory effects of exogenous and endogenous vaspin on 3T3-L1 adipocytes. Vaspin blunted IL-1β-induced expression and secretion of pro-inflammatory cytokines. Vaspin reduced cytokine-induced activation of intracellular NFκB signaling cascades. Vaspin increased insulin-stimulated phosphorylation of AKT.